2022
DOI: 10.1007/s12144-022-03938-7
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership and personal and job demands/resources: A person-centered approach and links with work-related subjective well-being

Abstract: The job demands-resources theory considers an open group of personal and job demands and resources. Thus, it allows us to include personal resources not yet covered (i.e., vigor at work) or less explored (i.e., emotional abilities), as well as personal demands not yet explored (i.e., overcommitment). Additionally, from this theory, it is proposed that leaders may influence employee wellbeing. Therefore, of particular interest is to analyze positive leadership styles, such as authentic leadership (AL). This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…From a person-centred perspective, various job demands and resources and personal resources have been used to obtain profiles of workers. Specifically, studies have identified profiles on the basis of participants' work engagement, burnout levels 27 and vigour at work among different job demands and resources, 28 whereas physical activity has mainly been used for identifying latent trajectories in workers, considering the frequency, intensity and duration of exercise, 29 or trajectories in the variation of physical activity during working and evening hours. 30 However, no study has yet used a combination of work engagement, vigour at work and different categories of physical activity to identify profiles using a person-centred approach and examine their impact on physical and psychological health.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…From a person-centred perspective, various job demands and resources and personal resources have been used to obtain profiles of workers. Specifically, studies have identified profiles on the basis of participants' work engagement, burnout levels 27 and vigour at work among different job demands and resources, 28 whereas physical activity has mainly been used for identifying latent trajectories in workers, considering the frequency, intensity and duration of exercise, 29 or trajectories in the variation of physical activity during working and evening hours. 30 However, no study has yet used a combination of work engagement, vigour at work and different categories of physical activity to identify profiles using a person-centred approach and examine their impact on physical and psychological health.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…The chosen design in terms of self-evaluated authenticity of a leader constitutes another added value to the body of authentic leadership literature. Previous studies largely relied on third-party evaluations when investigating the degree of authenticity of the leader (Hwang et al, 2022;Pulido-Martos et al, 2023). However, such external assessments of leaders' authenticity can never be as accurate as conducting self-evaluations of each leader.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…In a related vein, organizational performance outcomes such as followers' organizational commitment and work engagement were associated with authentic leadership (Hwang et al, 2022;Nair et al, 2022). Previous research has furthermore mainly focused on authentic leadership and its impact on general health outcomes such as subjective well-being (Pulido-Martos et al, 2023) but not with regard to eudaimonic well-being in the sense of self-actualization.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Employees led with an authentic leadership style tend to experience high intrinsic satisfaction, encouraging maximum contribution to their work (Chang et al, 2020;Pulido-Martos et al, 2023). Motivation arises from recognition, trust, and support (Dang & Chou, 2020), enhancing overall employee performance (Maryani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%